Assessment of cellulosic biomass saccharification by molten brönsted acidic 1-ethyl-3-methylimidazolium hydrogen sulphate ([EMIM][HSO4]) via kinetic studies - Ang, T.N.; Chan, C.H.; Ngoh, G.C.; Lee, K.M.; Yoon, L.W.; Chua, A.S.M. (North Carolina State University, 2016)
Ionic liquids have been employed to deconstruct and fractionate lignocellulosic biomasses because of their capacity to dissolve cellulose. However, there is limited literature reporting the use of ionic liquids in biomass saccharification, which mostly involves the addition of acid or water that conceals the true action of ionic liquid in saccharification. This article assesses the performance of molten Brӧnsted acidic 1-ethyl-3-methylimidazolium hydrogen sulphate ([EMIM][HSO4]) in saccharifying three agricultural biomasses, namely sago hampas, sugarcane bagasse, and rice husk, via saccharification kinetics. At 100 °C, [EMIM][HSO4] saccharification of the biomasses achieved equilibrium reducing sugar yields at various durations (sago hampas, 3 h; sugarcane bagasse, 1 h; rice husk, 5 h). The kinetic rate constant was obtained from model fitting, indicated that [EMIM][HSO4] showed a preference for saccharifying less recalcitrant sugarcane bagasse (37.9%) than sago hampas (7.0%) and rice husk (1.1%). Compared to H2SO4 saccharification, reducing sugar yields of [EMIM][HSO4] were consistently lower. The difference in yields might be attributed to the hydrous/anhydrous state of reaction and limited availability of component ions of the ionic liquid for dissolution and saccharification. This study demonstrates the feasible technical aspects of applying [EMIM][HSO4] to saccharify agricultural biomasses, which may lead to economic feasibility, recyclability, and cost effectiveness of ionic liquids in saccharification.